The analysis of an operating mode of the asynchronous generator with capacitor excitation - Postoronca S.; Berzan V.P.; Ermurachi Iu. (Problems of the Regional Energetics)
On the basis of a symbolical method of calculation of electric circuits the analysis of features of work of the three-phase asynchronous generator with two windings on статоре and capacitor excitation is executed. Results of the analysis of influence on a phase corner of a current and voltage of a windings of excitation of the generator are submitted at change of its loading from a mode of idling up to a mode of short circuit. Recommendations on stabilization of a target voltage of the generator are formulated at change of its loading.